The king’s justice: the rhetoric of executive clemency - Baker, Zachary (Kansas State University, 2021)
Towards the end of his term, President Donald Trump issued a series of pardons to political allies that strained democratic norms of executive accountability. Drawing on psychoanalytic theories of rhetoric, this thesis takes the position that Trump’s use of rhetoric in defense of his pardons constitutes a compensatory effort to obscure the contradictions between justice and Trump’s self-serving distortions. Trump’s pardons are rhetorical rituals that use tropes and metaphors to persuade audiences to support clemency in ways that are complicit with structural violence and detrimental to democracy. Three rhetorical strategies are identified: first, manipulation of the spheres of argument to alter audience expectations and evaluative criteria, second, counter-allegation to perform a ritual of masculine victimhood that coopts the voice and position of marginalized social groups, and third, subject construction under the trope of whiteness in the service of narratives of racial insecurity.
Keywords: Executive clemency; Donald Trump; Rhetoric